2005
DOI: 10.1144/0016-764904-029
|View full text |Cite
|
Sign up to set email alerts
|

Testing tectonic models with geochemical provenance parameters in greywacke

Abstract: A variety of models has been proposed for the origin of late Devonian low-grade greywacke, juxtaposed with the high-grade Variscan basement of the Black Forest. Here we interpret detrital zircon ages, and geochemical and Sm–Nd isotopic data of greywacke samples as evidence for their sources and tectonic setting of deposition. Detrital zircon ages of 371–384 Ma reveal igneous activity shortly before the deposition of the greywacke sequence at c . 365 Ma. ε Nd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the case of greywackes, the major element compositions vary significantly within and across different tectonics regimes (Barnes 1990;Floyd et al 1990;Korsch et al 1993;Banerjee & Bhattacharya 1994;Gill et al 1994;Gu 1994;McDaniel et al 1994;Duller & Floyd 1995;Roser et al 1996;Hayashi et al 1997;Holail & Moghazi 1998;Kalsbeek et al 1998;Hegner et al 2005;Wanas & Abdel-Maguid 2006;Kiminami & Fujii 2007;Dostal & Keppie 2009). Collisional orogenesis typically involves passive margin turbidites and subordinate amounts of arc-derived greywackes.…”
Section: Phase Equilibria Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of greywackes, the major element compositions vary significantly within and across different tectonics regimes (Barnes 1990;Floyd et al 1990;Korsch et al 1993;Banerjee & Bhattacharya 1994;Gill et al 1994;Gu 1994;McDaniel et al 1994;Duller & Floyd 1995;Roser et al 1996;Hayashi et al 1997;Holail & Moghazi 1998;Kalsbeek et al 1998;Hegner et al 2005;Wanas & Abdel-Maguid 2006;Kiminami & Fujii 2007;Dostal & Keppie 2009). Collisional orogenesis typically involves passive margin turbidites and subordinate amounts of arc-derived greywackes.…”
Section: Phase Equilibria Modellingmentioning
confidence: 99%
“…Collisional orogenesis typically involves passive margin turbidites and subordinate amounts of arc-derived greywackes. Thus, for the modelling in this study an average chemical composition of 33 passive margin greywackes that have SiO 2 of 69-76 wt% and Na 2 O >1.5 wt% was chosen (McDaniel et al 1994;Roser et al 1996;Kalsbeek et al 1998;Hegner et al 2005;Dostal & Keppie 2009; Table 1) and 15% of the iron was assumed to be ferric.…”
Section: Phase Equilibria Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…These ages can be linked to several very different sources. One potential source may be the Black Forest, and related complexes, where Variscan and Caledonian ages are equally abundant in late Devonian greywackes (Hegner et al 2005). Another option is a derivation from the mid-German crystalline rise.…”
Section: U-pb Zircon Agesmentioning
confidence: 99%
“…They concluded an undifferentiated Devonian time for the deposition of the Protocanites Beds, whilst the Ordovician and Silurian fossils were regarded as recycled (Hann and Sawatzki 1998, p. 186, 188). In subsequent papers, Hann et al (2003), Vaida et al (2004) and Hegner et al (2005) regarded the Protocanites greywackes as Late Devonian to Early Carboniferous in age, while Brockamp et al (2015), without providing evidence, suggested an early Viséan age. Already earlier, Schaltegger (2000) Kalt et al 2000).…”
Section: The Stratigraphic Age Of the Protocanites Bedsmentioning
confidence: 99%